2019
DOI: 10.5114/aoms.2018.77769
|View full text |Cite
|
Sign up to set email alerts
|

Effect of N-acetylcysteine on intimal hyperplasia and endothelial proliferation in rabbit carotid artery anastomosis

Abstract: IntroductionNeointimal hyperplasia due to smooth muscle cell migration and proliferation, as well as extracellular matrix accumulation, plays an important role in stenosis and restenosis that develop after reconstructive vascular interventions. Various agents are being tested to reduce neointimal hyperplasia and to prevent lumen stenosis. In the present study, the effect of N-acetylcysteine (NAC) on intimal hyperplasia and endothelial hyperplasia after carotid anastomosis was investigated in a rabbit model.Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…As seen in the literature, the intima thickness, the media thickness, the I/M thickness ratio, the intima area, the media area, the I/M area ratio, the lumen diameter and the lumen area are the comparable variables for histological evaluation of neointimal hyperplasia. [23][24][25][26][27] We also used these histological measurements in our study. We found that intimal hyperplasia was significantly lower in the BSAglutaraldehyde and in the PEG polymer group compared to the Control group (p < 0,05).…”
Section: Discussionmentioning
confidence: 99%
“…As seen in the literature, the intima thickness, the media thickness, the I/M thickness ratio, the intima area, the media area, the I/M area ratio, the lumen diameter and the lumen area are the comparable variables for histological evaluation of neointimal hyperplasia. [23][24][25][26][27] We also used these histological measurements in our study. We found that intimal hyperplasia was significantly lower in the BSAglutaraldehyde and in the PEG polymer group compared to the Control group (p < 0,05).…”
Section: Discussionmentioning
confidence: 99%
“…Sepsis, trauma, pancreatitis, acute myocardial infarction, tissue perfusion, and endogenous antioxidants are depleted. NAC plays a role in the defense mechanism by removing free radicals and replacing the depleted antioxidant glutathione (Bakker et al 1994;Kavala et al 2019). In addition, NAC was found to have a protective role in hypoxia-related cell injury of the liver (Heil et al 2018), ionizing radiation-induced liver failure (Mansour et al 2008), ischemic liver injury in rats (Kalimeris et al 2016), and toxic liver damage (Mendonça et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Carotid artery stenosis is triggered by the formation of plaque within the carotid artery, which supplies blood to the brain. Such atherosclerotic pathology can proceed silently from the simple thickening of the carotid intima-media to the symptomatic stenosis [ 17 ]. In later stages, plaques can mature and often become unstable, rupture, and lead to acute ischaemic events.…”
Section: Discussionmentioning
confidence: 99%